1995
DOI: 10.1111/j.1600-0536.1995.tb00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐activity relationships in allergic contact dermatitis

Abstract: Primin (2-methoxy-6-pentyl-1,4-benzoquinone) is a naturally-occurring strong sensitizer from Primula obconica (Primulacease). To determine the effect of side-chain length on sensitizing potency, 15 analogues with linear side chains from C1 to C15 and 4 C6-analogues with branched side chains were prepared synthetically and devoted to experimental sensitization in guinea pigs. The results showed an increase of the sensitizing capacity with increasing length of the alkyl side chain from C1 to C10, reaching a maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In a number of sensitization experiments 2-methoxy-6-alkyl-1,4-benxoquinones with branch side chain length C1-C15, including primin, have showed an increase of the sensitizing capacity with increasing length of the alkyl side chain from C-1 to C-13 (reaching maximum activity at an alkyl chain of 10 to 11 carbons), but the sensitizing potency decreased beyond 13 carbons and the sensitization hardly occurred at C-1 to C-3. Similar results were also obtained from studies on non-quinonoid compounds like catechols, phenols, hydroquinones, and gallates (Roberts et al, 1991;Konig et al, 1993;Hausen et al, 1995). In this study, all major compounds with branch side chains identified from the wild P. obconica in China were shown to be 1 or 2 carbons in length.…”
Section: Resultssupporting
confidence: 87%
“…In a number of sensitization experiments 2-methoxy-6-alkyl-1,4-benxoquinones with branch side chain length C1-C15, including primin, have showed an increase of the sensitizing capacity with increasing length of the alkyl side chain from C-1 to C-13 (reaching maximum activity at an alkyl chain of 10 to 11 carbons), but the sensitizing potency decreased beyond 13 carbons and the sensitization hardly occurred at C-1 to C-3. Similar results were also obtained from studies on non-quinonoid compounds like catechols, phenols, hydroquinones, and gallates (Roberts et al, 1991;Konig et al, 1993;Hausen et al, 1995). In this study, all major compounds with branch side chains identified from the wild P. obconica in China were shown to be 1 or 2 carbons in length.…”
Section: Resultssupporting
confidence: 87%
“…This compound is not restricted to Primula sp., and has also been isolated from several other plants, e.g., Miconia (Melastomaceae) [6 -8] and Iris (Iridaceae) species [9]. The sensitizing effect of primin and other p-benzoquinones has been ascribed to the covalent binding of a receptor protein of epidermal cells to C(3) and C(5) of the quinone ring system, which could be attacked by nucleophiles of the receptor protein [10] [11]. We previously undertook several binding experiments with primin and 2-phenylethylamine and amino acids to investigate the mechanistic outcome of this addition reaction [12].…”
mentioning
confidence: 99%
“…The synthesis of primin (1) was first reported by Schildknecht et al in 1967 1 and later by de Lima et al 5 Primin (1) and some of its homologous alkyl analogs were subsequently prepared for structure-biological activity relationships. [14][15][16] Key steps in recent syntheses (Scheme 1) involved the addition of an alkyl Grignard to 2-hydroxy-3-methoxybenzaldehyde (3) to form the benzyl alcohol 4, 5,14 and ortho-lithiation of tetrahydropyranyl guaiacol (5) yielding 6 (ca. 60% overall yield to 1).…”
mentioning
confidence: 99%